Mapping non-laminar proton acceleration in laser-driven target normal sheath field. (29th November 2022) - Qin, C. Y.; Zhang, H.; Li, S.; Zhai, S. H.; Li, A. X.; Qian, J. Y.; Gui, J. Y.; Wu, F. X.; Zhang, Z. X.; Xu, Y.; Liang, X. Y.; Leng, Y. X.; et al.
Abstract: We report on experimental observation of non-laminar proton acceleration modulated by a strong magnetic field in laser irradiating micrometer aluminum targets. The results illustrate the coexistence of ring-like and filamentation structures. We implement the knife edge method into the radiochromic film detector to map the accelerated beams, measuring a source size of 30–110 μm for protons of more than 5 MeV. The diagnosis reveals that the ring-like profile originates from low-energy protons far off the axis whereas the filamentation is from the near-axis high-energy protons, exhibiting non-laminar features. Particle-in-cell simulations reproduced the experimental results, showing that the short-term magnetic turbulence via Weibel instability and the long-term quasi-static annular magnetic field by the streaming electric current account for the measured beam profile. Our work provides direct mapping of laser-driven proton sources in the space-energy domain and reveals the non-laminar beam evolution at featured time scales.